PENGARUH TERAPI SEKANDI (SENAM KAMAR MANDI) TERHADAP KEBUGARAN JASMANI PADA INDIVIDU USIA PRODUKTIF - Rachmania, Diana; Perwiditasari, Rentika (Journal Nursing Care and Biomolecular, 2017)
Introduction: There is a decrease of interest in doing exercise because of the crowded activity.Than so many people who complain about his health both physical and psychological. sekandi therapy (gymnastic bathroom therapy) is a gymnastics exercise with regulation of breathing and pranayama exercises become the foundation of it. The purpose of this study was to determine the effect of Sekandi therapy to increased physical fitness in individuals of productive age. Method: This research used quasy experiment desain. The samples were 40 respondents, taken by Pruposive sampling technique, and divided into 2 groups: control group (n = 20) and treatment group (n = 20). Result:  The results of the control group without treatment as much as 70% of the physical fitness therapy in the enough category. And the  treatment group after they aplly sekandi therapy almost all respondents for physical fitness in the good category as much as 80%. Wilcoxon test result with p value 0,000 < α (0,05) and Mean Whitney with  p value 0,025 <α (0,05) indicate there was influence of Sekandi therapy (gymnastics bathroom therapy) to increase physical fitness in individual age productive. Analysis: Through  sekandi therapy, can increase the work activities of the heart, respiratory system, maximize the bodys metabolic functions, eliminate muscle stiffness so that the body in good health.  Discussion: Sekandi  therapy in addition to beneficial in terms of health can also provide benefits in other respects in particular can be used as an additional movement in gymnastics fitness such as aerobics.